ANALYSIS OF DIFFICULTIES STUDENT OF CLASS XI IPS SMA TARUNA NUSANTARA IN READING HIRAGANA - Listriani, Listriani; Diner, Lispridona; Nurhayati, Silvia (Universitas Negeri Semarang, 2018)
This study aims to determine the difficulty, causal factors, and solutions to overcome difficulties in reading hiragana experienced by students of class XI IPS SMA Taruna Nusantara. The approach used in this research is quantitative approach using descriptive research method. The sample in this research is the students of class XI IPS SMA Taruna Nusantara who take the subjects cross the interest of Japanese language amounted to 19 students. The technique of collecting data used is questionnaire. Based on the research results can be concluded that students’ difficulties are reading the symbols of sokuon sounds, distinguishing similar hiragana letters, reading the yoo’on sounds, reading the handakuon sounds, and reading the dakuon sounds. The factors are the lack of students’ ability to read hiragana properly, the lack of reference books owned by students to practice reading hiragana, the lack of ability of students in solving the problem of reading hiragana in a timely manner, and the lack of hiragana reading practice outside of Japanese language lessons. The solution to overcome those difficulties are that students are expected to arrange the time when completing the test question of hiragana, students are expected to increase the practice of reading hiragana outside of Japanese language lessons, and students are expected to be more creative by adding reference books other than Sakura’s book to practice reading hiragana, such as Nihongo Kana Nyuumon and Marugoto.   Penelitian ini bertujuan untuk mengetahui kesulitan, faktor penyebab, dan solusi untuk mengatasi kesulitan dalam membaca hiragana yang dialami oleh siswa kelas XI IPS SMA Taruna Nusantara. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan kuantitatif dengan menggunakan metode penelitian deskriptif. Sampel pada penelitian ini adalah siswa kelas XI IPS SMA Taruna Nusantara yang menempuh mata pelajaran lintas minat bahasa Jepang dengan jumlah 19 siswa. Teknik pengumpulan data yang digunakan adalah menggunakan angket. Berdasarkan hasil penelitian dapat disimpulkan bahwa kesulitan siswa adalah membaca lambang bunyi sokuon, membedakan huruf hiragana yang bentuknya mirip, membaca lambang bunyi yoo’on, membaca lambang bunyi handakuon, dan membaca lambang bunyi dakuon. Faktor penyebabnya adalah kurangnya kemampuan siswa dalam membaca hiragana dengan tepat, kurangnya referensi buku yang dimiliki siswa untuk berlatih membaca hiragana, kurangnya kemampuan siswa dalam menyelesaikan soal ulangan membaca hiragana dengan tepat waktu, dan siswa kurang berlatih membaca hiragana di luar jam pelajaran bahasa Jepang. Solusi untuk mengatasi kesulitan tersebut adalah siswa diharapkan dapat mengatur waktu saat menyelesaikan soal ulangan membaca hiragana, siswa diharapkan memperbanyak latihan membaca hiragana di luar jam pelajaran bahasa Jepang, dan siswa diharapkan lebih kreatif dengan menambah referensi buku selain buku Sakura untuk berlatih membaca hiragana, seperti Nihongo Kana Nyuumon dan Marugoto.